The Chinese Moral Cultivation - Ma, Wen; Zhu, Yaqin; Chunli, Li; Zhang, Bo; Tian, Xin (Advances in Social Sciences Research Journal, 2023)
Historically, the Confucian classics tell us the importance of moral practices. Presently, educators are concerned about how to cultivate well-developed individuals. In this paper, I introduce the examples of Chinese moral cultivation. At group level, morality can be practiced from things such as maintaining public health system; caring and protecting public construct and tools; and devoting to public good. At personal level, moral practice can be exercised by the belief of what you do not want done to yourself do not do to others; to blame oneself severely and to blame others lightly; and do not fear the strong and insult the weak. Here I intend to clarify the existence and development of human feelings and wisdom must rely on society. From this point of view, we get a clear idea of why the relations between all things that human creates and society is closely related.